1996
DOI: 10.1002/(sici)1097-0320(19960201)23:2<97::aid-cyto2>3.0.co;2-i
|View full text |Cite
|
Sign up to set email alerts
|

Flow cytometry of mesophyll and bundle sheath chloroplast thylakoids of maize (Zea mays L.)

Abstract: Chlorophyll fluorescence at short and long wave‐lengths was used to sort thylakoid membranes of maize, a plant with the C4 dicarboxylic acid pathway of photosynthesis, in a flow cytometer. The method yielded two distinct particle populations that were identified as mesophyll and bundle sheath thylakoids by low‐temperature fluorescence spectroscopy and by the pigment ratio of chlorophyll a/b. Mesophyll and bundle sheath thylakoids were essentially pure after sorting by flow cytometry. Fluorescence data and chlo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…For fluorescence measurements, diluted leaf powder was prepared according to Weis (1985) with modifications described by Pfündel & Pfeffer (1997). Fluorescence excitation spectra were recorded at a low temperature (77 K) using an LS 50B (Perkin Elmer, Buckinghamshire, UK) as specified earlier ( Pfündel & Meister 1996).…”
Section: Methodsmentioning
confidence: 99%
“…For fluorescence measurements, diluted leaf powder was prepared according to Weis (1985) with modifications described by Pfündel & Pfeffer (1997). Fluorescence excitation spectra were recorded at a low temperature (77 K) using an LS 50B (Perkin Elmer, Buckinghamshire, UK) as specified earlier ( Pfündel & Meister 1996).…”
Section: Methodsmentioning
confidence: 99%
“…Cross‐sections of 20–40 μm thickness were prepared using a cryo‐microtome (Leica CM3050‐Cryostat, Leica Instruments GmbH) at –15 °C, and collected on poly‐ L ‐lysine‐coated slides (Sigma, St Louis, Missouri, USA). Probably, the freeze–thaw cycle could affect the chloroplast ultra‐structure; however, flow cytometric investigations showed that even membrane particles released from chloroplasts were unaltered in their fluorescence properties ( Pfündel & Meister 1996). Hence, structural changes during sample preparation do not affect the fluorescence signal that we consider here.…”
Section: Methodsmentioning
confidence: 99%
“…Preparations enriched in either mesophyll or bundle sheath chloroplasts were obtained according to Höfer, Santore & Westhoff (1992) with the modifications specified in Pfündel & Meister (1996). Flow cytometrical analysis of chloroplasts was done with a FACStar Plus sorting flow cytometer (Becton Dickinson, San Jose, California, USA) as described previously ( Pfündel & Meister 1996). Chlorophyll fluorescence of single particles was excited by 488 nm light from an argon ion laser operated at 500 mW output power.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although grossly disorganized, there was less evidence of chloroplast swelling in the BS cells of lls1 leaves. This may be because of the differential sensitivities of the chloroplast types to ROS or a differential ability of the BS chloroplasts to produce ROS because they lack the oxygen-generating PSII found in mesophyll chloroplasts (Pfuendel and Meister, 1996;Kingston-Smith and Foyer, 2000). Lower ROS production could result in less damage to BS cells and this could explain why the autocatalytic spread of lls1 lesions is retarded near vascular elements.…”
Section: Loss Of Chloroplast Structural Integrity Is a Key Event In Lmentioning
confidence: 99%